THE ACCEPTABILITY OF INDONESIAN TRANSLATED POEMS :A Case Study of Goenawan Mohammad's Translated Poems - Eka Herdiana Susanto, - (2012)
This study entitled The Acceptability of Indonesian Translated Poems(A Case Study of Goenawan Mohammad Translated Poems)is aimed at knowing about the acceptability of Indonesian poems that are translated into English by Indonesian translator, LaksmiPamuntjak. It is also aimed at knowing the response to the poems from native speakers: Indonesian and English. This study investigated the responses of the native speakers of both languages by asking questions about the poems to them. The data were obtained from document analysis of six respondents consisted of two English speakers and four Indonesian speakers. The theory that is proposed by Bressler was used to analyze the reader response and Venuti's theory was used to analyze the translation strategy that was used by the translator. The translating strategy is investigated by doing textual analysis. Even though there are many translation strategies, but one of the most significant translation strategies in the finding of this study is domestication strategy. The purpose of using domestication strategy is to make the level of acceptability become high.